Physical Conditions Of House And Community Behavior Analysis Of Acute Respiratory Tract Infection In Working Region Central Public Health Soe City South East Central District - Dacosta Barros, Santino; Indasah; Yudhana, Amarin (Journal of Global Research in Public Health, 2019)
The incidence of acute respiratory infections occurs due to poor air environmental conditions both inside and outside the home environment. The purpose of this study to analyze the physical condition of the house and the behavior of the community against the occurrence of acute respiratory infections in the work area of ​​Soe City Central Public Health East Central South District. This research design is correlational analytic with Cross sectional approach. The population studied by all ISPA patients in Soe City Public Health Central of South East Central District Regency with 358 people, with Simple Random Sampling technique obtained 189 respondents. Independent variable of house physical condition (Ventilation X1, X2 Lighting, X3 density, Floor type X4), community behavior X5 with dependent variable of acute respiratory infections occurrence. Data collection using observation. Data analysis with Ordinal Regression test, α = 0,05. The result of this research shows that almost half of the respondents have sufficient category behavior, that is 73 respondents (38,6%) and most of respondent have mild category of ISPA, that is 114 respondent (60,3%). Result of Ordinal Regression analysis simultaneously known there is influence of house physical condition and behavior of society collectively to ISPA event in work area of ​​Soe City Health Center South East Middle Regency (p-value = 0,000 < = 0,05). Partially, there is the effect of ventilation (p = 0,030), lighting (p = 0,030), occupancy density (p = 0,043), floor type (p = 0,049), and community behavior (p = 0,014) Environmental conditions that do not meet the health requirements will reduce the air quality in the room, the condition is exacerbated the lack of public behavior in maintaining environmental hygiene so that the air in the house a good place for the development of virus causes acute respiratory infections. Therefore it is expected for health institutions concerned to participate in improving the quality of public health by doing counseling related to healthy home and acute respiratory tract infection prevention behavior.